Mutation spectrum of congenital heart disease in a consanguineous Turkish population - Dong, Weilai; Kaymakcalan, Hande; Jin, Sheng Chih; Diab, Nicholas S.; Tanıdır, Cansaran; Yalcin, Ali Seyfi Yalim; Ercan‐Sencicek, A. Gulhan; Mane, Shrikant; Gunel, Murat; Lifton, Richard P.; Bilguvar, Kaya; Brueckner, Martina (Molecular genetics & genomic medicine, 2022)
Backgrounds While many studies agree that consanguinity increases the rate of congenital heart disease (CHD), few genome analyses have been conducted with consanguineous CHD cohorts. Methods We recruited 73 CHD probands from consanguineous families in Turkey and used whole‐exome sequencing (WES) to identify genetic lesions in these patients. Results On average, each patient had 6.95 rare damaging homozygous variants, 0.68 of which are loss‐of‐function (LoF) variants. Seven patients (9.6%) carried damaging homozygous variants in five causal CHD genes. Six of those patients exhibited laterality defects (six HTX and one D‐TGA). Three additional patients (4.1%) harbored other types of CHD‐associated genomic alterations, which overall explained 13.7% (10/73) of the cohort. The contribution from recessive variants in our cohort is higher than 1.8% reported from a cohort of 2871 CHD subjects where 5.6% of subjects met the criteria for consanguinity. Conclusions Our WES screen of a Turkish consanguineous population with structural CHD revealed its unique genetic architecture. Six of seven damaging homozygous variants in CHD causal genes occur in the setting of laterality defects implies a strong contribution from consanguinity to these defects specifically. Our study thus provided valuable information about the genetic landscape of CHD in consanguineous families in Turkey. WES screen of 73 CHD probands from consanguineous unions in Turkey revealed that 13.7% of cases can be explained by genomic alterations, especially homozygous variants. Our study thus provided valuable information about the genetic landscape of CHD in consanguineous families in Turkey.